Analyzing the Anglo-American Hegemony in the Times Higher Education Rankings - Kaba, Amadu Jacky (Education Policy Analysis Archives, 2012)
This study analyzes the 2009 Times Higher Education-QS top 200 universities in the world. Based on this analysis the study claims that the THS reflects the phenomenon of Anglo-American hegemony. The United States with 54 universities and the United Kingdom with 29 dominated the THS. In addition, six out of every ten universities on the top 200 list were located in countries that were at one time partly or fully colonized by the United Kingdom. This study identifies a number of factors that contributed to a country having at least one university ranked on the list: Age of an institution, endowment of an institution, the size of a nation’s population, gross domestic products (GDP) and GDP per capita, level of international trade (exports/imports), colonial heritage and language.